2016
DOI: 10.5194/hess-20-1483-2016
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic extremes – an intercomparison of multiple gridded statistical downscaling methods

Abstract: Abstract. Gridded statistical downscaling methods are the main means of preparing climate model data to drive distributed hydrological models. Past work on the validation of climate downscaling methods has focused on temperature and precipitation, with less attention paid to the ultimate outputs from hydrological models. Also, as attention shifts towards projections of extreme events, downscaling comparisons now commonly assess methods in terms of climate extremes, but hydrologic extremes are less well explore… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
83
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 82 publications
0
83
0
Order By: Relevance
“…For temperature we applied an additive correction and for precipitation a multiplicative correction to avoid artificial generation of negative precipitation values. Many previous studies follow the same approach when applying bias correction techniques (e.g., Addor et al, ; Teutschbein & Seibert, ; Werner & Cannon, ).…”
Section: Methodsmentioning
confidence: 99%
“…For temperature we applied an additive correction and for precipitation a multiplicative correction to avoid artificial generation of negative precipitation values. Many previous studies follow the same approach when applying bias correction techniques (e.g., Addor et al, ; Teutschbein & Seibert, ; Werner & Cannon, ).…”
Section: Methodsmentioning
confidence: 99%
“…The atlas uses monthly values of precipitation and surface mean temperatures simulated by 29 GCMs, which have spatial resolutions ranging from about 1°× 1°to over 2.5°× 2.5°(latitude × longitude). We downscale daily temperatures and precipitation amounts simulated by 24 of these GCMs (all models for which daily values were available at the time of analysis; see Table S3) to~10 km resolution over Canada using the BCCAQ method described by Murdock et al (2014) and Werner and Cannon (2016). We considered the RCP2.6, the RCP4.5, and the RCP8.5 emission scenarios (van Vuuren et al 2011) for the future projections.…”
Section: Methodsmentioning
confidence: 99%
“…The plots compare the quantiles of the gridded observational data (horizontal axis) with the quantiles of station observations (vertical axis, left column), raw GCM output (vertical axis, central column), and downscaled GCM output (vertical axis, right column) bias-correction/spatial disaggregation (BCSD; Wood et al 2004) were evaluated as a followup to the downscaling intercomparison by Bürger et al (2012Bürger et al ( , 2013. A method called BCCAQ, which combines downscaling by BCCA with bias correction by trend-preserving quantile mapping (Cannon et al, 2015), was found to produce the most robust projections according to a set of tests that measure day-to-day temporal sequencing, equality of distributions, and spatial co-variability (Murdock et al 2014;Werner and Cannon 2016). Evaluation was performed via temporal split-sample validation with multiple reanalyses standing in for GCMs (Werner and Cannon 2016), as well as a Bperfect model^setup (Dixon et al 2016) in which spatially degraded RCM projections stand in for GCMs to test robustness under future climate conditions (Murdock et al 2014).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinku et al, 2008;Asadullah et al, 2008), North America (e.g. Tian et al, 2009;West et al, 2007), South America (e.g. Vila et al, 2009), and China (e.g.…”
Section: Scope and Objectivesmentioning
confidence: 99%